Encephalomyelitis Caused by Balamuthia mandrillaris in a Woman With Breast Cancer: A Case Report and Review of the Literature - Hu, Juan; Zhang, Yiqi; Yu, Yongwei; Yu, Huili; Guo, Siruo; Shi, Ding; He, Jianqin; Hu, Chi; Yang, Jiqi; Fang, Xueling; Xiao, Yonghong (Frontiers in Immunology, 2022)
Balamuthia mandrillaris is one cause of a rare and severe brain infection called granulomatous amoebic encephalitis (GAE), which has a mortality rate of >90%. Diagnosis of Balamuthia GAE is difficult because symptoms are non-specific. Here, we report a case of Balamuthia amoebic encephalomyelitis (encephalitis and myelitis) in a woman with breast cancer. She sustained trauma near a garbage dump 2 years ago and subsequently developed a skin lesion with a Mycobacterium abscessus infection. She experienced dizziness, lethargy, nausea and vomiting, inability to walk, and deterioration of consciousness. Next generation sequencing of cerebrospinal fluid (CSF) samples revealed B. mandrillaris, and MRI of both brain and spinal cord showed abnormal signals. T cell receptor (TCR) sequencing of the CSF identified the Top1 TCR. A combination of amphotericin B, flucytosine, fluconazole, sulfamethoxazole, trimethoprim, clarithromycin, pentamidine, and miltefosine was administrated, but she deteriorated gradually and died on Day 27 post-admission.